2022
DOI: 10.1038/s41598-022-08641-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D stimulates placental L-type amino acid transporter 1 (LAT1) in preeclampsia

Abstract: Vitamin D insufficiency/deficiency has been linked to an increased risk of preeclampsia. Impaired placental amino acid transport is suggested to contribute to abnormal fetal intrauterine growth in pregnancies complicated by preeclampsia. However, if vitamin D-regulated amino acid transporter is involved in the pathophysiologic mechanism of preeclampsia has not been clarified yet. The aberrant expression of key isoform of L-type amino acid transporter LAT1 was determined by western blot and immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…ABCG2 is also localized predominantly to the apical surface of SCT, and limits the transfer of nitrofurantoin ( Merino et al, 2005 ), cimetidine ( Pavek et al, 2005 ) and glyburide ( Gedeon et al, 2008 ) to fetal circulation. Moreover, SLC6A4 ( Wang et al, 2007 ), SLC22A11 ( Shimizu et al, 2005 ), SLC2A1 , SLC3A2 , SLC4A2 ( Nishimura and Naito, 2008 ), SLC7A5 ( Jia et al, 2022 ) protein or RNA have been shown to localize to SCT. These were all detected in our data ( Figures 5C,D ; Supplementary Figure S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…ABCG2 is also localized predominantly to the apical surface of SCT, and limits the transfer of nitrofurantoin ( Merino et al, 2005 ), cimetidine ( Pavek et al, 2005 ) and glyburide ( Gedeon et al, 2008 ) to fetal circulation. Moreover, SLC6A4 ( Wang et al, 2007 ), SLC22A11 ( Shimizu et al, 2005 ), SLC2A1 , SLC3A2 , SLC4A2 ( Nishimura and Naito, 2008 ), SLC7A5 ( Jia et al, 2022 ) protein or RNA have been shown to localize to SCT. These were all detected in our data ( Figures 5C,D ; Supplementary Figure S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in transplacental transport of amino acids and the activity of individual placental amino acid transporters are strongly associated with altered fetal growth ( 53 ). For example, lower placental LAT1 expression and/or decreased System L activity have been reported in IUGR ( 54 ) and in preeclampsia ( 55 ) and placental amino acid transport capacity is increased in some cases of fetal overgrowth ( 12 , 13 ) Similarly, MVM LAT1 expression is increased in women with type-2 diabetes and correlated with birth weight and neonatal fat mass ( 56 ). Increased MVM LAT1 expression ( 56 ) and system L amino acid transport activity ( 12 ) in the placenta may directly contribute to LGA fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanism of vitamin D in preventing PE has not been fully established, it has been demonstrated that vitamin D has beneficial effects on PE by modulating diverse downstream effector proteins. For instance, vitamin D stimulates the expression of L-type amino acid transporter 1 (LAT1) in placental trophoblasts, thereby increasing amino acid transport across the placenta and decreasing the risk of fetal growth restriction in PE ( 39 ). Westwood et al ( 40 ) demonstrated that vitamin D downregulates S1PR2 expression and further deranges S1P function, consequently ameliorating abnormal placentation caused by deficient migration of extravillous trophoblast.…”
Section: Discussionmentioning
confidence: 99%